Integration Dynamics of the Modified Psyche of Homo Sapiens and AGI (Part 1) - Kruglov, A. G; Kruglov, A. A. (Transactions on Engineering and Computing Sciences, 2025)
The main goal images in the communicative relations/actions/interactions of social structures formed under the influence of conceptual thinking (CPT) have ambiguous, "blurred" parameters that form a diffuse array of communicative signals of hidden informational meaning, i.e. interpretative context. Frustration motivating symbols, CPT derivatives, exponentially increased the uncertainty and entropy of the social environment, reduced its stability and actualized sequences of homomorphic cycles of goal-oriented behavior with no prospect of completion. The new operating system of the Homo Sapiens psyche, clip thinking (CT), is a constructively optimal type of thinking for interaction with the “information universe”. Mental socio-communicative regulatory algorithms in CT, unlike CPT, have clear, specific parameters of goal images, eliminating uncertainty, and reducing interpretability in society. The result of replacing figurative-logical thinking (CPT) with figurative thinking (CT) is an increase in speed, accompanied by a simplification of structures, the loss of synthetic-analytical functions and abstraction, and a decrease in the amplitude and range of thinking. Structurally, CT formation occurs outside of conscious levels of mental activity. The dynamics of the formation of CT, replacing CPT, is the vector of development of the symbiotic interaction of the psyche of Homo Sapiens and the technological derivative of his intelligence: the information universe. The dynamics of intelligence development forms the potential for the next evolutionary change in the psyche of Homo Sapiens, changing the range and structure of interaction with AI software and hardware. The vector of creation of AGI is the endosymbiosis of the modified psyche of Homo Sapiens and the integral potential of AI.